PEMISAHAN AMIL ALKOHOL DARI LIMBAH CAIR LUTTER WASHER - Ani Purwanti (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
Fusel oil is a side product of ethanol manufacturing process through the fermentation of molasses. Sometimes, fusel oil is accidently mixed with liquid waste from the bottom of alcohol rectifying column. This mixture is called lutter washer. Fusel oil contains isoamyl alcohol, n-amyl alcohol, and other alcohols. Isoamyl alcohol is the raw material of organic ester. Further processing is required to increase the economic value of fusel oil, such as the separation of components by distillation. In this study, the composition of isoamyl alcohol and n-amyl alcohol in the residue in the distillation process as a function of distillation time in a packing column was evaluated. An artificial waste lutter washer was used as a raw materials in this experiment. The processes were conducted using a distillation column with a cylindrical dan spherical glass packing materials. Lutter washer was distilled with total reflux until the equilibrium temperature was reached, then the data of the experiment was taken during 180 minutes at the condition of reflux at 5/5 (5 minutes distillate was returned to the tower and 5 minutes distillate was collected). The composition of the distillation residue were evaluated at interval time of 30 minutes. The same processes were evaluated using different heights of packing materials. The data show that the highest composition of isoamyl alcohol and n-amyl alcohol are 21.99% and 3.70% of the 15 mL total residue, respectively. It is obtained in the distillation process that used the packing materials with ball shape, the column with 85 cm of height and 3.5 cm of diameter.